Implementation of Goods and Services Tax (GST): a study on perspective and spending habits among students / Nur Athirah Ismadi - Ismadi, Nur Athirah (2019)
According to Nur Suriana, Mohd Saifi, Nor Suhaily, & Suhaimi (2015), the implementation of Goods and Services Tax (GST) on 1st April 2015 by the Malaysian government devotes towards various perceptions and effect either negatively or positively from Malaysian society. The main problem to be focused on here is that government applied GST and it is an obligation on every society members nevertheless their status while the fact is that those students have no source of income. This is because the government did not make any exemption on students regarding the GST payment. Thus, the main objectives of this research are to study on student’s perspective towards implementation of GST and to study on student’s spending habits after the implementation of GST. This study implements quantitative approach with the use of survey questionnaires through Google Form as the main tool of data collection where 66 of ACIS Diploma Students of Part 5 were selected as respondents of this study. Data collected was analysed using descriptive analysis. Generally, finding of this study shows that majority of the students were still in the phase of uncertainty towards the implementation of GST, while some of them mostly had an effort taking the positive steps to start listing and budgeting in their spending habits after the implementation of GST.